Tabligh in the Perspective of Thematic Hadith: A Conceptual Framework for Knowledge Dissemination and Its Implications for Library Science Development - Touku Umar; Abustani Ilyas; Erwin Hafid (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2026)
This article examines the concept of tabligh from the perspective of thematic hadith as a basis for formulating a conceptual framework for knowledge dissemination in Library Science. This study aims to map the construction of the meaning of tabligh in the hadiths of the Prophet Muhammad (peace be upon him) and to formulate an ethical framework for knowledge dissemination that is relevant to the development of library practices. This study employs a qualitative approach using a literature review method and thematic hadith analysis (maudhu‘i). The primary data consist of hadiths concerning the obligation to convey knowledge, the prohibition of concealing knowledge, and scientific responsibility, which are analyzed using content analysis techniques. The findings reveal three main thematic classifications within the concept of tabligh: (1) the normative-transformative dimension, which emphasizes the moral obligation to convey knowledge; (2) the communicative-epistemic dimension, which demands accuracy, clarity, and source validity; and (3) the social-beneficial dimension, which is oriented toward accessibility and public benefit. Based on this mapping, the study formulates an ethical framework for knowledge dissemination grounded in tabligh values, positioning librarians as both moral agents and information mediators. These findings extend the study of Islamic information ethics from a predominantly normative approach toward a conceptual formulation that is applicable within the context of Library Science development. Abstrak Artikel ini mengkaji konsep tabligh dalam perspektif hadis tematik sebagai dasar perumusan kerangka konseptual diseminasi pengetahuan dalam Ilmu Perpustakaan. Penelitian ini bertujuan untuk memetakan konstruksi makna tabligh dalam hadis Nabi Muhammad saw. serta merumuskan formulasi kerangka etis diseminasi pengetahuan yang relevan bagi pengembangan praktik perpustakaan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan dan analisis hadis tematik (maudhu‘i). Data utama berupa hadis-hadis tentang kewajiban menyampaikan ilmu, larangan menyembunyikan pengetahuan, serta tanggung jawab keilmuan, yang dianalisis menggunakan teknik analisis isi. Hasil penelitian menunjukkan adanya tiga klasifikasi tematik utama dalam konsep tabligh: (1) dimensi normatif-transformatif, yang menekankan kewajiban moral penyampaian ilmu; (2) dimensi komunikatif-epistemik, yang menuntut akurasi, kejelasan, dan validitas sumber; serta (3) dimensi sosial-kemaslahatan, yang berorientasi pada aksesibilitas dan kebermanfaatan publik. Berdasarkan pemetaan tersebut, penelitian ini merumuskan kerangka etis diseminasi pengetahuan berbasis nilai tabligh yang menempatkan pustakawan sebagai agen moral sekaligus mediator informasi. Temuan ini memperluas kajian etika informasi Islam dari pendekatan normatif menuju formulasi konseptual yang aplikatif dalam konteks pengembangan Ilmu Perpustakaan.